Dynamic Evolution of Toll-Like Receptor Multigene Families in Echinoderms - Buckley, Katherine M.; Rast, Jonathan P. (Frontiers in Immunology, 2012)
The genome of the purple sea urchin, Strongylocentrotus purpuratus, was the first to be sequenced from a long-lived large invertebrate. Analysis of this genome uncovered a surprisingly complex immune system in which the moderately sized sets of pattern recognition receptors that form the core of vertebrate innate immunity are encoded in large multigene families. The sea urchin genome contains 253 Toll-like receptor (TLR) genes, more than 200 Nod-like receptors and 1095 scavenger receptor cysteine-rich domains, a ten-fold expansion relative to vertebrates. Given their stereotypic structure and simple intron-exon architecture, the TLRs are the most tractable of these families for more detailed analysis. An immune defense role for these receptors is suggested by their sequence diversity and expression in immunologically active tissues, including phagocytes. This complexity of the sea urchin TLR multigene families largely derives from expansions that are independent of those in vertebrates and protostomes, although a small family of TLRs with structure similar to that of Drosophila Toll likely originated in an ancient eumetazoan ancestor. Several other invertebrate deuterostome genomes have been sequenced, including the cephalochordate, Branchiostoma floridae and the sea urchin Lytechinus variegatus, as well as partial sequences from two other sea urchin species. Here, we present an analysis of the invertebrate deuterostome TLRs with emphasis on the echinoderms. Representatives of most of the S. purpuratus TLR subfamilies and homologs of the protostome-like sequences are found in L. variegatus. The phylogeny of these genes within sea urchins highlights lineage-specific expansions at higher resolution than is evident at the phylum level. These analyses identify quickly evolving TLR subfamilies that are likely to have novel functions and other, more stable, subfamilies that may function similarly to those of vertebrates.